Night Drop : The American Airborne Invasion of Normandy - Marshall, S. L. A. 1900-1977 (Boston An Atlantic Monthly Press Book, 1962)
Story of the men of the 82d and 101st airborne divisions who parachuted by night into Normandy, and fought for the success of D-Day.
Include Maps, Epilogue and Index
Keywords: World War (1939-1945) -- France--Normandy